The Politics of Enmity: Deconstruction and the New Neoconservatism - Mookerjee, Robin (Revista de Letras, 2009)
In Specters of Marx, Derrida turns his attention to the “spectral” impulse in Marx and fi nds time to chide neoconservative theorist Francis Fukuyama for his “messianic” leanings. This episode highlights the problematic character of Derrida’s relationship to competing political persuasions. Since the writing of Specters, French theory, through its infl uence on discourses around identity and postcolonialism, has contributed to the increased polarization of America’s political spectrum. With Derrida’s notion of “messianism” as a starting point, this essay examines recent neoconservative works. Due to the tendency of academic intellectuals to eschew a clear subject position, conservative intellectuals have stepped out of conversation with the left and turned their attention to Europe. Their recent polemics either withdraw from Fukuyama’s messianic historicism, viewing it as the province of an endemically “fascist” left, or reclaim messianism with the diagnosis of a European “illness.” Through such a diagnosis, these authors have found a tangible enemy in Europe’s relatively traditional political culture. At the same time, they have projected the “moral relativism” of America’s deconstructive academy onto the Continental political establishment. Keywords: Deconstruction. Politics. Neoconservatism. Messianism. Historicism.